PELATIHAN PEMBUATAN MEDIA PEMBELAJARAN BIOLOGI BERBASIS INTERNET BAGI GURU BIOLOGI SMA DI KABUPATEN SLEMAN - Hinuhili, dkk, Victoria (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2009)
Abstract Information technology has progressed rapidly. The using of information technology can help teachers to manage their time for searching references that can be useful to teach their students. This programme was aimed to give a course for biology teachers of Senior High Schools at Sleman District to use information technology for making lessoning media based on internet. The methode of this course was learning by doing. The team gave the theory about information technology using for media making, and then the participants practiced it directly. There were 16 teacher participants from Sleman District, and one teacher from East Kalimantan as a guest teacher. The participants were very eager to search the information related their teaching tasks. They did searching, browsing, downloading, and uploading the information from internet and then they arranged it in a lessoning media. In a limited trying test, lessoning media created by the participants could help the teaching-learning process clearly, but it needed time more to prepare and to arrange the media. Keywords: lessoning media and internet